Does the use of a knee brace change the biomechanics during a badminton lunge to the net, and what are the implications to injury mechanisms? - Valldecabres, R.; de Benito, A. M.; Littler, G.; Richards, J. (Valencia Catholic University `San Vicente Mártir, 2018)
The aim of this study was to determine changes in knee biomechanics during badminton lunges due to fatigue, lunge strategy and knee bracing. Kinetic and kinematic data were collected from sixteen experienced right-handed badminton players. Three factor repeated measures ANOVAs (lunge direction - fatigue - brace) were performed with Least Significant Difference pairwise comparisons. In addition, clinical assessments including; Y-balance test, one leg hop distance and ankle dorsiflexion range of motion were performed pre and post fatigue. The knee showed significantly greater flexion during the forehand lunge compared to backhand. In contrast, the internal rotation velocity and the knee extension moment were greater during backhand. Knee angular velocity in the sagittal plane, peak knee moment and range of moment in the coronal plane and stance time showed significantly lower values post fatigue. In addition, the peak knee adduction moment showed significantly lower values in the braced condition in both the fatigued and non-fatigues states, and no significant differences were seen for peak vertical force, loading rate, approach velocity, or in any of the clinical assessment scores. There appears to be greater risk factors when performing a backhand lunge to the net compared to a forehand lunge, and proprioceptive bracing appears to reduce the loading at the knee.